Statics of Magnetic Fluid Drop with Compound Magnetic Core in a Wedge-Shaped Channel - V. Bashtovoi; S. Klimovich; А. Motsar; A. Reks; P. Ryapolov; A. Storozhenko; I. Shabanova (Журнал нано- та електронної фізики)
A behavior of magnetic fluid drop with compound magnetic core in a wedge-shaped channel was studied experimentally. The study examines influence of magnetic fluid properties, its volume and magnetic field on statics of the system compound magnet – magnetic fluid drop in wedge-shaped channel. The possibility to change the static conditions of such system by altering magnetic field of the core was observed